(untitled) (Diametros, 2018)
The debate over whether brain death is death has focused on whether individuals who have sustained total brain failure have satisfied the biological definition of death as “the irreversible loss of the integration of the organism as a whole.” In this paper, I argue that what it means for an organism to be integrated “as a whole” is undefined and vague in the views of those who attempt to define death as the irreversible loss of the integration of the organism as a whole. I show how what it means for a living thing to be integrated as a whole depends on the sortal (kind) concept by which it is identified. Since interests, values, and ontological considerations besides strictly biological ones affect the concepts by which we individuate and identify living things, those non-biological considerations have a bearing on what it means for a particular kind of living thing to exist as a whole and thus what it means for one of us to die. Even if our bodies may remain organically integrated in some sense despite total brain failure, this fact should not lead us to reject brain death as death. Artificially sustained brain-dead human bodies are not human beings, but the remains of them. While such bodies may be alive in some sense, they are not human beings or human persons. They are not one of us.